Effect of day length on the development of tubers in yams (Dioscorea spp.) - Shiwachi, H.; Ayankanmi, T.G.; Asiedu, Robert (2002)
Sixty-day-old plants of white Guinea yam (Dioscorea rotundata), water yam (D. alata) and yellow Guinea yam (D. cayenensis) were exposed to 10 h day lengths (short days) for 15 and 30 days. Short-day treatment applied at the early growth stage of yams promoted the enlargment of tubers, but the responses varied among species and cultivars. The photoperiodic sensitivities of D. rotundata and D. alata were lower than for D. cayenensis. Early-maturing cultivars were lower in photoperiodic sensitivity than the late ones. Short day length is a major factor in the enlargement and maturation of yam tubers. It appears that day length treatments could be used to distinguish between early-and late-maturing cultivars of yams.